TEAM MEMBER FUNCTIONAL BACKGROUND AND INVOLVEMENT IN MANAGEMENT TEAMS: DIRECT EFFECTS AND THE MODERATING ROLE OF POWER CENTRALIZATION. - Bunderson, J. S. (Academy of Management Journal, 2003)
This article examines the relationship between a team member's functional background and two forms of intrateam involvement: centrality in a team's workflow and involvement in team decision making....